Revisiting gradient wind balance in tropical cyclones using dropsonde observations - Garcia-Franco, J; Schwendike, J (Wiley, 2020)
This study diagnoses the degree of gradient wind balance (GWB) in dropsonde observations of 30 tropical cyclones (TCs) divided into 91 intense observation periods. The diagnosed GWB in these observation periods are composited to investigate which characteristics of a TC are significantly related to departures from GWB. This analysis confirms that on average the flow above the boundary layer is approximately in GWB. Supergradient flow is more common near the radius of maximum wind (RMW) in the upper boundary layer than above in the free troposphere or outside the RMW and is also more common in strong storms than in weak storms. In contrast, the degree of GWB does not differ between intensifying, steady‐state and weakening storms. Storms with a peaked wind profile have a higher probability of showing supergradient winds than those with a flat wind profile. The comparison of two commonly used functions to fit observations shows that the diagnosing GWB from dropsonde observations is highly dependent on the analysis technique. The agradient wind magnitude and even sign is shown to depend on which of these functions is used to fit the observations. The use of a polynomial fit consistently diagnoses the presence of supergradient winds far more frequently than a piece‐wise function, and also shows a marked degree of imbalance above the boundary layer. Therefore, caution is warranted when determining the degree of GWB with a polynomial fit.